2012
DOI: 10.1126/scitranslmed.3003162
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-Based Postnatal Therapy for Neuroinflammation and Cerebral Palsy in a Rabbit Model

Abstract: Cerebral palsy (CP) is a chronic childhood disorder with no effective cure. Neuroinflammation, caused by activated microglia and astrocytes, plays a key role in the pathogenesis of CP and disorders such as Alzheimer’s disease and multiple sclerosis. Targeting neuroinflammation can be a potent therapeutic strategy. However, delivering drugs across the blood-brain-barrier to the target cells for treating diffuse brain injury is a major challenge. Here, we show that systemically administered polyamidoamine dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
427
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(443 citation statements)
references
References 53 publications
15
427
0
1
Order By: Relevance
“…In vitro studies have revealed that these nanoparticles possess the ability to inhibit the fibrillation and aggregation of proteins involved in neurodegenerative disorders [7][8][9]. Importantly, in vivo studies of polyamidoamine (PAMAM) dendrimers have been performed to determine their toxicity to the central nervous system [10], check their ability to localize in inflammatory cells in the brain [11], and show their potential in dendrimer-drug conjugates for the treatment of neuroinflammation [12,13]. Significant progress has been made in research on the interactions between dendrimers and living cells or organisms, resulting in commercially available products such as transfection agents (SuperFect from Qiagen and PrioFect from EMD-Merck), markers for rapid heart attack diagnosis (Stratus CS Acute Care from Siemens Healthcare), and anthrax-detecting agents (Alert Ticket from the US Army Research Laboratory) [3].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have revealed that these nanoparticles possess the ability to inhibit the fibrillation and aggregation of proteins involved in neurodegenerative disorders [7][8][9]. Importantly, in vivo studies of polyamidoamine (PAMAM) dendrimers have been performed to determine their toxicity to the central nervous system [10], check their ability to localize in inflammatory cells in the brain [11], and show their potential in dendrimer-drug conjugates for the treatment of neuroinflammation [12,13]. Significant progress has been made in research on the interactions between dendrimers and living cells or organisms, resulting in commercially available products such as transfection agents (SuperFect from Qiagen and PrioFect from EMD-Merck), markers for rapid heart attack diagnosis (Stratus CS Acute Care from Siemens Healthcare), and anthrax-detecting agents (Alert Ticket from the US Army Research Laboratory) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies with PAMAM dendrimers in a rat model suggested that, in healthy eyes, the dendrimers were readily cleared from the retina upon intravitreal administration. In contrast, in the presence of retinal degeneration, the dendrimer was retained in the retina, mostly localized to the activated microglial cells even up to 30 days (Kannan et al, 2012). Such selective localization in cells associated with neuroinflammation may help the toxicity profile of these dendrimers.…”
Section: Dendritic Macromoleculesmentioning
confidence: 88%
“…There is no nanoparticle applied in clinic yet, at the same time, there is less report about the osmotic pressure and quality control of nanoparticles. Kettiqer et al (Kannan et al, 2012) reported that the silica nanoparticles may have potential hazards to cells. In addition, many kinds of nanoparticles are not stable.…”
Section: The Safety Of Nanoparticlesmentioning
confidence: 99%
“…Moreover, surface modification of dendrimers leads to a more efficient in vivo administration. Hydroxyl-functionalized generation-4 PAMAM dendrimers selectively localized in neurons and activated microglia in the injured brain and retina when administered intravenously to newborn rabbits [59], or to 6-12-month-old dogs [53]. One of the problems that arise following the functionalization of dendrimers to reduce toxicity is the observed decrease in diffusion and in cellular uptake of the dendrimers and their payload.…”
Section: Dendrimersmentioning
confidence: 99%